Interventions to Prevent Prison Violence: A Scoping Review of the Available Research Evidence - Day, Andrew (The prison journal, 2022)
Although a reasonably large body of knowledge is now available to describe prison violence, much less is known about the effectiveness of violence prevention interventions. In this scoping review, ten different research databases were searched to identify recent evaluation studies that adopted an experimental or quasi-experimental design. A total of 18 separate evaluation studies met the study inclusion criteria which were then categorised in relation to whether they aimed to address individual, situational, or social drivers of violence. The strength and utility of the evidence base in terms of selecting and implementing new prevention initiatives in prison settings is considered.